2014
DOI: 10.1111/tra.12228
|View full text |Cite
|
Sign up to set email alerts
|

SpatTrack: An Imaging Toolbox for Analysis of Vesicle Motility and Distribution in Living Cells

Abstract: The endocytic pathway is a complex network of highly dynamic organelles, which has been traditionally studied by quantitative fluorescence microscopy. The data generated by this method can be overwhelming and its analysis, even for the skilled microscopist, is tedious and error-prone. We developed SpatTrack, an open source, platform-independent program collecting a variety of methods for analysis of vesicle dynamics and distribution in living cells. SpatTrack performs Endocytosis of proteins from the cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…C4P and E4Pac were imaged either in the same channel or in the blue (DAPI) channel using the Leica filter A-cube of excitation: 360 nm (20-nm bandpass); dichroic: 400-nm; and emission: 425-nm longpass. The same filter cube is often used for imaging the sterol-binding polyene antibiotic filipin (Lund et al, 2014). TopFluor-cholesterol was imaged on the same system using a standard fluorescein filter set [470-nm, (20-nm bandpass) excitation filter, 510-nm longpass dichromatic filter and 537-nm (23-nm bandpass) emission filter].…”
Section: Fluorescence Microscopy and Image Analysismentioning
confidence: 99%
“…C4P and E4Pac were imaged either in the same channel or in the blue (DAPI) channel using the Leica filter A-cube of excitation: 360 nm (20-nm bandpass); dichroic: 400-nm; and emission: 425-nm longpass. The same filter cube is often used for imaging the sterol-binding polyene antibiotic filipin (Lund et al, 2014). TopFluor-cholesterol was imaged on the same system using a standard fluorescein filter set [470-nm, (20-nm bandpass) excitation filter, 510-nm longpass dichromatic filter and 537-nm (23-nm bandpass) emission filter].…”
Section: Fluorescence Microscopy and Image Analysismentioning
confidence: 99%
“…2, 3 and 9). We observed previously an increased contribution of active transport to the mobility of NPC2 containing vesicles over the course of cholesterol efflux 21 . This active transport will shift the steady state distribution of LE/LYSs towards the PM thereby accelerating further sterol exchange and cellular release ( Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Supporting that notion, we measured a selective release of DHE over fluorescent NPC2 on a per-vesicle basis suggesting that NPC2 is largely retained in LE/LYSs during sterol efflux. Previously, we reported that LE/LYSs containing Alexa546-NPC2 became increasingly mobile and moved preferentially by active transport in the course of lysosomal cholesterol mobilization 21 . Increased motility, repositioning and tubulation of LE/LYSs have been recently reported as being intimately linked to restoration of LE/LYS function in lysosomal storage diseases 57,58 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations